2016
DOI: 10.1080/14693062.2016.1160864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the EU 10% interconnection target in the context of CO2 mitigation

Abstract: The European Commission has proposed the target of achieving an interconnection capacity of at least 10% of the installed electricity production capacity for each Member State by 2020 in the context of the envisaged Energy Union. The underlying objectives are to increase the security of supply at affordable prices via market integration and to contribute to decarbonization by accommodating an increasing level of renewable generation. In this article we have assessed whether this target could effectively fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This result is similar to some results reported by research on other countries. To strengthen the energy security of EU member states, the European Commission formulated the concept of building an energy alliance, however, Mezősi et al (2016) find that such an alliance will ultimately lead to an increase in carbon emissions. Moreover, filtering geographical distance would not change our conclusion that market integration significantly promotes a reduction in carbon emissions, while the coefficient of integ 1 decreases only 38.81 percent compared to integ 2.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…This result is similar to some results reported by research on other countries. To strengthen the energy security of EU member states, the European Commission formulated the concept of building an energy alliance, however, Mezősi et al (2016) find that such an alliance will ultimately lead to an increase in carbon emissions. Moreover, filtering geographical distance would not change our conclusion that market integration significantly promotes a reduction in carbon emissions, while the coefficient of integ 1 decreases only 38.81 percent compared to integ 2.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Jaraite [8] claim that the EU ETS did not promote CO 2 emissions reduction, whereas it slightly reduced CO 2 intensity. Mezosi [9] demonstrate that the present low carbon price under the EU ETS makes carbon-intensive electricity systems run on higher utilization rates and consequently increases CO 2 emissions. Laing [10] point out that the effects of EU ETS on low-carbon technology innovation and investment remain uncertain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, increasingly, there has been a focus on how interconnection can increase trade among member states and, in doing so, improve the efficiency of markets and, ultimately, social welfare [35]. A crucial argument in favor of interconnectors is that they further the integration of intermittent power resources [35][36][37], as they can help to reduce the impact of renewable penetration on price volatility [38,39].…”
Section: Interconnectors: Role In Single Electricity Marketsmentioning
confidence: 99%
“…There has already been an ongoing discussion of the impact of interconnection on electricity markets and CO 2 emissions [45][46][47]. Mezősi, Pató, and Szabó [38] argued that the effect of interconnectors on CO 2 emissions is dependent on the carbon price and the ratio between coal prices and gas prices. Indeed, they found that complying with the 10% interconnection target by 2020 would lead to an increase in CO 2 emissions, if the low CO 2 price environment prevailed.…”
Section: Interconnectors: Role In Single Electricity Marketsmentioning
confidence: 99%